Transição de estado na cerâmica supercondutora (Hg,Re–1223), com a existência de duas fases coexistentes - Eleutério, Fernando Henrique Santos (2017)
The goal this work is the investigation of the two intrinsic phases of structural superconductors, using the magnetic response and its granular composition. By investigating the magnetic susceptibility to AC in the polycrystalline pottery of the mercury base doped with rhenium ((Hg0.82Re0.18Ba2Ca2Cu3O8.16 – (Hg,Re)-1223) - (Hg, Re) - 1223) with the precursor with optimum oxygen content, pulverized (reduced to powder and sieved) it was possible to determine the critical temperature of the sample and to observe that it depends on the size of each of the grain. For the 20 µm particle only a critical temperature of 133K was found. But it had two critical temperatures (133K and 98K) as the particle size is further reduced to a mesoscopic scale of 600nm. This fact was elucidated by an extension of the Ginzburg-Landau theory using two order parameters to parameterize the complex scalar field and making the connection with the microscopic model responsible for describing the peculiarities of these types of grains.